Optimising Household Solid Waste Collection Facility in Autonomous Regions of Developing Countries: A Case Study on Karanganyar Regency, Indonesia - Eko Setiawan; Juang Victorio Kusuma; Ganang Adi Sulistyawan; Septin Puji Astuti (Forum Geografi)
In many developing countries, autonomous regencies have significant rights to establish and manage waste collection facilities that are critical in conveying waste to final disposal sites. However, limited budgets often restrict these rights, particularly at the community level, where waste management needs are more acute. Given the growing importance and emergence of waste-related issues over the years, this study addresses the urgent challenge of siting household solid-waste collection facilities within the context of an autonomous region. We propose several location-allocation models namely a waste-weighted P-median, a pure P-median, a P-centre, a P-dispersion, and a “distance gap” model- to opti-mise the siting of these facilities. Utilising data from Karanganyar Regency in Indonesia, we demons-trate that the optimal model for facility siting is contingent on the specific objectives of the initiative, such as minimising transportation costs or maximising service coverage. Our findings underscore the need for enhanced planning around high-capacity waste collection facilities, emphasising their pivotal role in addressing the future demand for household waste management in autonomous regions. This study provides a framework for policymakers to make informed decisions about siting waste facilities and promote sustainable waste management practices in resource-constrained environments. Including more autonomous regions, a variety of scenarios on population growth and waste generation, additio-nal perspectives on waste management, environmental and social considerations, and the investigation of emerging technologies in waste management are suggested as areas for future research.